2015
DOI: 10.1109/tpwrs.2014.2340911
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sizing of Energy Storage for Regenerative Braking in Electric Railway Systems

Abstract: The problem of optimally sizing hybrid energy storage systems (HESS) installed in electric railway systems, considering the effect of regenerative braking is studied in this paper. HESSs combine traditional batteries and newly developed ultracapacitors, taking advantage of the high energy capacity of batteries and of the flexibility and ability to capture high power density of ultracapacitors. A novel mixed integer linear programming formulation that includes the counting of battery cycles is presented. Some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(58 citation statements)
references
References 20 publications
0
58
0
Order By: Relevance
“…HESS is proposed with the intention of combining the batteries and UC to obtain both high energy and power density, and thus has an obvious advantage over the single type of energy storage system, especially for the application of peak load shaving and regenerative braking power absorbing in the high-speed railway system. In general, the UC's advantage of long cycle life and fast response make it suitable to capture the railway power peaks and valleys in high frequency, while batteries are more suited for low frequency operation [31,32]. Accordingly, HESS is adopted in this study for the better energy saving performance.…”
Section: Hybrid Energy Storage Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…HESS is proposed with the intention of combining the batteries and UC to obtain both high energy and power density, and thus has an obvious advantage over the single type of energy storage system, especially for the application of peak load shaving and regenerative braking power absorbing in the high-speed railway system. In general, the UC's advantage of long cycle life and fast response make it suitable to capture the railway power peaks and valleys in high frequency, while batteries are more suited for low frequency operation [31,32]. Accordingly, HESS is adopted in this study for the better energy saving performance.…”
Section: Hybrid Energy Storage Systemsmentioning
confidence: 99%
“…With regard to HESS, lead-acid (LA) batteries and UCs are considered in this study. All parameters associated with HESS are presented in Table 2 [31,32,47,57]. It is assumed that the service period of this project is 20 years and all the HESS-related devices can serve for the entire project period except for batteries.…”
Section: Cases Description and Input Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameter of cost function related to SC energy c 2 Parameter of cost function related to losses c 3 Parameter of cost function related to the energy exchanged with the distribution system E loss Total loss energy E pv,p…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…In the recent past, the scientific community has been paying growing attention to the different uses of these technologies in urban and suburban railway traction systems (streetcar, light rail transit, and mass rapid transit) [1,2]. In fact, it has been widely demonstrated that their use enables both the under sizing of the power supply plant in the project stage or a more intensive use of existing subsystems without major modifications (e.g., the repowering of electrical substations and the increase of the cross-sectional area of contact wires), and besides it definitely allows to improve the overall energy efficiency thanks to the recovery of the braking energy and its subsequent release in the starting phase of the traction motors.…”
Section: Introductionmentioning
confidence: 99%